2021
DOI: 10.2196/28852
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence and Directions for Future Research in eHealth Physical Activity Interventions for Adults Affected by Cancer: Systematic Review

Abstract: Background Physical activity (PA) interventions can increase PA and improve well-being among adults affected by cancer; however, most adults do not meet cancer-specific PA recommendations. Lack of time, facility access, and travel distances are barriers to participation in PA interventions. eHealth technologies may address some of these barriers, serving as a viable way to promote PA behavior change in this population. However, no review from July 2018 has synthesized available evidence across eHea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 127 publications
1
38
0
Order By: Relevance
“… 20 Indeed, a recent review on eHealth interventions in cancer proposed videoconferencing as a way to deliver accessible, virtually supervised interventions. 22 In the current study, supervision involved weekly virtually supervised workouts in small group settings and regular participant/specialist check-ins using videoconferencing through HEAL-Me. This allowed for live feedback on exercise form/technique and facilitated discussions that informed exercise adaptations and tailored education/advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Indeed, a recent review on eHealth interventions in cancer proposed videoconferencing as a way to deliver accessible, virtually supervised interventions. 22 In the current study, supervision involved weekly virtually supervised workouts in small group settings and regular participant/specialist check-ins using videoconferencing through HEAL-Me. This allowed for live feedback on exercise form/technique and facilitated discussions that informed exercise adaptations and tailored education/advice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, eHealth interventions are being increasingly researched in the field of exercise oncology. 22 Recent trials have found eHealth interventions to be feasible and acceptable in older adults with cancer, 23 , 24 individuals with thoracoabdominal malignancies, 25 and individuals with metastatic prostate cancer. 26 Other trials identify the promise of eHealth interventions for outcomes such as fatigue, strength, pain, and functional capacity in various cancer populations.…”
Section: Introductionmentioning
confidence: 99%
“…Teleprehabilitation was defined in a previously published commentary by our group in 2020 [ 5 ] as the use of technologies to deliver health interventions to patients prior to surgery. Briefly, the commentary elaborated on the benefits and opportunities of using various technological tools available [ 14 , 15 ]. The commentary suggested that combined systems of videoconferencing and wearable devices may be optimal in providing personalized feedback [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective PA interventions for adults with cancer include in-person and home-based programs, individual and group formats, and interventions that feature technology-based behavior change support (Ester, Eisele, et al, 2021;Sheeran et al, 2019). In line with the ever-increasing popularity and capability of internet-connected devices, efforts to use technology to support PA behavior change are gaining attention (Vandelanotte et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research and development related to PA mobile apps for adults with cancer and other populations has seen rapid growth in recent years (Chan et al, 2020b;Ester, Eisele, et al, 2021;Vandelanotte et al, 2016). For all those who have toyed with the idea, this viewpoint article details the authors' recent experiences with app development in exercise oncology and presents recommendations for future work in this field.…”
Section: Introductionmentioning
confidence: 99%